Improving the flame retardance and melt dripping of poly(lactic acid) with a novel polymeric flame retardant of high thermal stability. (8th August 2016) - Shi, Xiaowei; Liao, Fenghui; Ju, Yaqing; Dai, Xiu; Cao, Yu; Li, Jiawei; Wang, Xinlong
Summary: A polymeric flame retardant containing phosphorus and nitrogen (PCNFR) was synthesized and characterized by Fourier transform infrared spectroscopy, nuclear magnetic resonance and gel permeation chromatography. The thermal decomposition temperatures at 10% weight loss ( T 10 wt% ) of PCNFR were around 358 °C, and the char yield at 600 °C reached about 60 wt% both in nitrogen and air by thermogravimetric analysis. The flame retarded poly(lactic acid) (PLA) composites with PCNFR were prepared. The thermogravimetric analysis results showed that PCNFR could improve the thermal stability of the flame retarded PLA composites with low loading (≤10 wt%) and at high temperature zone (≥390 °C). The condensed products from the decomposition of the flame retarded composites at 380 °C and 450 °C for different intervals were analyzed by Raman spectroscopy, and the results showed that time and temperature influenced the structure of the char residue evidently. When incorporating 30 wt% PCNFR into PLA, the limited oxygen index of the flame retarded composites reached 25.0%, and V‐0 rating was achieved. The char residues were analyzed by scanning electron microscopy, Fourier transform infrared spectroscopy and X‐ray photoelectron spectroscopy in detail. Copyright © 2016 John Wiley & Sons, Ltd.